Die Lehre von den Seelenpotenzen bei Durandus von Saint-Pourçain: eine philosophische Psychologie im Übergang vom Hoch- zum Spätmittelalter - Jeschke, Thomas (Studien und Texte zur Geistesgeschichte des Mittelalters, 2022)
"In his doctrine of the soul and its faculties, Durandus of Saint-Pourçain adopts important features of medieval philosophical psychology and at the same time develops an independent and coherent theory, which is paradigmatic for the turn from High to Late Middle Ages"